Investor Satisfaction through Service Quality: An Evidence of Pokhara Based Brokerage Firms - Adhikari, Nabin Bahadur; Adhikari , Bidhan (Journal of Nepalese Business Studies, 2024)
The capital market depends heavily on the brokerage sector, which mediates securities transactions. This article examines at the level of service quality offered by Nepalese brokerage houses in Pokhara and how it affects investors’ satisfaction. The study focuses on more than two independent factors, including responsiveness, assurance and reliability, as well as how they related to and affect the dependent variable, which is investor satisfaction. This empirical work has utilized the primary data, were collected through survey with 105 respondents by following rules of thumb. Most of the questions were closed ended and 5-point likert scales. The convenience sampling method was applied for conducting this work. The descriptive as well as inferential statistics were used to conclude the research work and SPSS version were utilized. Most of the respondents were male (60%), age group of 20-29 were highest, most of the respondents were Bachelor pass, most of the respondent were students, income level as less than 20k per month and most of the respondents do have experience of 1-2 year of secondary market. There is a significant relationship between RE, RP, AS with IS. The relationship between RE and IS, AS and IS are statistically significance at the level of 0.05. But, the second hypothesis is rejected because (RP and IS) the p value higher is than 0.005. Hence, we can conclude that, there is a significant positive association between RE, RP, AS and IS. There is significant impact of reliability of service and assurance of the brokerage firm on the level of investor satisfaction. Hence, the investors are satisfied by the reliability of service and assurance from the brokerage firm in Pokhara. It is concluded that the brokerage firm has to give provide reliable service and assurance to the investor for their satisfaction.